Cardioprotective effects of timosaponin B II from Anemarrhenae asphodeloides Bge on isoproterenol-induced myocardial infarction in rats. (5th October 2015) - Deng, Xue-Yang; Chen, Jun-Jun; Li, Hong-Yan; Ma, Zhan-Qiang; Ma, Shi-Ping; Fu, Qiang
Abstract: The aim of the present study was to investigate the cardioprotective effects of Timosaponin B II (TB), a main bioactive constituent from Anemarrhenae asphodeloides Bge, on an isoproterenol (ISO)-induced myocardial infarction model in rats and explore its underlying mechanisms. Rats were treated with TB (50 mg/kg, 100 mg/kg) or diltiazem hydrochloride (DH, 5 mg/kg) by gastric gavage for five days. At the 4th and 5th days, myocardial injury was induced by ISO injection (85 mg/kg) at an interval of 24 h for 2 consecutive days. After the induction, rats were anaesthetized with pentobarbital sodium (30 mg/kg) to record the electrocardiogram. Our research showed that ISO administration resulted in significant elevations in the ST-segment, the levels of cardiac injury biomarkers creatine kinase-MB (CK-MB) and lactate dehydrogenase (LDH), and concentrations of serum proinflammatory cytokines interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α). Pretreatment with TB significantly reversed these alterations induced by ISO challenge. The cardioprotective effects of TB were further proved by the histopathological examination. Exploration of the underlying mechanisms of its actions revealed that TB pretreatment restored the ISO-induced decrease of super oxide dismutase (SOD) and the increase of malondialdehyde (MDA). Meanwhile, we found that the enhancement of antioxidant defense system might be associated with the increased heme oxygenase isoform 1 (HO-1) induction and activated nuclear respiratory factor 2 (Nrf-2) translocation. Furthermore, the present research also demonstrated that nuclear translocation of Nrf-2 and subsequent HO-1 expression might be associated with nuclear factor kappa B (NF-κB) pathway activation. Taken together, our finding demonstrated that TB might have a potential benefit in preventing ischemic heart diseases like myocardial infarction. Highlights: Timosaponin B II (TB) showed cardioprotective effects. TB exhibited antioxidant and anti-inflammatory activities. TB inhibited NF-κB pathway while activated the Nrf-2/HO-1 pathway.